Autophagy-Dependent Secretion: Contribution to Tumor Progression - Keulers, Tom G.; Schaaf, Marco B. E.; Rouschop, Kasper M. A. (Frontiers in Oncology, 2016)
Autophagy is best known as a lysosomal degradation and recycling pathway to maintain cellular homeostasis. During autophagy, cytoplasmic content is recognized and packed in autophagic vacuoles, or autophagosomes, and targeted for degradation. However, during the last years, it has become evident that the role of autophagy is not restricted to degradation alone but also mediates unconventional forms of secretion. Furthermore, cells with defects in autophagy apparently are able to reroute their cargo, like mitochondria, to the extracellular environment; effects that contribute to an array of pathologies. In this review, we discuss the current knowledge of the physiological roles of autophagy-dependent secretion, i.e., the effect on inflammation and insulin/hormone secretion. Finally, we focus on the effects of autophagy-dependent secretion on the tumor microenvironment (TME) and tumor progression. The autophagy-mediated secreted factors may stimulate cellular proliferation via auto- and paracrine signaling. The autophagy-mediated release of immune modulating proteins changes the immunosuppresive TME and may promote an invasive phenotype. These effects may be either direct or indirect through facilitating formation of the mobilized vesicle, aid in anterograde trafficking, or alterations in homeostasis and/or autonomous cell signaling.